Saber y conocimiento : una aproximación plural (2008)
ABSTRACT: The aim of this paper is to show how knowledge, in the sense of certainty, has received criticisms from several disciplines (philosophy, psychology, psychoanalysis, epistemology, biology, among others), which has implicated a re-formulation of some perspectives about it. The difference between knowing and knowledge, already examined by several authors, is tackled here from a point of view that shows the possibility of reflection about knowing and knowledge taken from contemporary epistemology in psychology, ethics, philosophy, and other fields. This text is divided into five sections: a) Theory and practice: The main topic is introduced along with the problem of the connection between theory and practice and their diffuse limits, which is the beginning of criticism about knowledge in its positivistic form, b) Some assumptions about knowledge and its transmission: this second part discusses several assumptions about knowledge that gave shape to the traditional idea about it, c) Outlook of science in the XX century in relation to the problem of knowledge: this section presents a panoramic view of the criticisms made by contemporary epistemology about the concept of knowledge assumed by logical positivism, d) Tacit knowledge: this part deals in detailed manner with one of the stronger criticisms that has ever been made to the positivistic conception of knowledge: tacit knowledge. Moreover, a distinction between knowing and knowledge is proposed, e) Conclusion: The present situation of knowing and knowledge as an effect of the route designed throughout this text is shown in this section, taking into account some reflections about Plato and his distinction between doxa and episteme (terms which to some extend could be equivalent to knowing and knowledge, respectively- Ramírez, 1996; Lopera, 2004).